Cognitive function and risperidone long-acting injection vs. paliperidone palmitate in schizophrenia: a 6-month, open-label, randomized, pilot trial. Issue 1 (December 2016) - Takekita, Yoshiteru; Koshikawa, Yosuke; Fabbri, Chiara; Sakai, Shiho; Sunada, Naotaka; Onohara, Ai; Nishida, Keiichiro; Yoshimura, Masafumi; Kato, Masaki; Serretti, Alessandro; Kinoshita, Toshihiko
Abstract Background Recently, long-acting injection (LAI) of second-generation antipsychotics has become a valuable strategy for the treatment of schizophrenia. However, few studies have compared the effects of different LAI antipsychotics on cognitive functions so far. The present study aimed to compare the influence of risperidone LAIs (RLAI) and paliperidone palmitate LAIs (PP) on cognitive function in outpatients with schizophrenia. Methods In this 6-month, open-label, randomized, and controlled study, 30 patients with schizophrenia who were treated with RLAIs were randomly allocated to the RLAI-continued group or the PP group. At baseline and 6 months, the patients were evaluated using the Brief Assessment of Cognition in Schizophrenia (BACS) that was the primary outcome of the study. The Subjective Well-being under Neuroleptic drug treatment-Short form (SWNS), the Positive and Negative Syndrome Scale (PANSS), and the Drug-Induced Extrapyramidal Symptoms Scale (DIEPSS) scores were secondary outcome variables and they were tested at the same time points. Results The two groups did not differ in terms of PANSS, DIEPSS, or SWNS total score changes. However, the BACS score for the attention and processing speed item showed higher improvement in the PP group than the RLAI group (p  = 0.039). Conclusions The results of this preliminary study suggest that PPs may improve attention and processing speed more than RLAIs. Anyway, a replication in a larger and double-blind study is needed. Trial registration UMIN000014470 . Registered 10 July 2014